Paraguay : Financial Sector Review - World Bank (Washington, DC, 2013)
The report examines the highly vulnerable situation of the financial system in Paraguay, which suffered from a banking crisis in 1995-98, in addition to recent competitive devaluations of the Brazilian currency, the fall in cotton prices, as well as the regional economic slowdown. A major factor obscuring the reality of banking system solvency, is the practice of substituting needed loan provisions, with collaterals which underlie the loans. The main issue here is the relative liquidity absence, and delays inherent in unwinding such collateral, as well as its potential over-valuation, making it an ineffective substitute for cash provisions. The report further examines banking reforms, and restructuring of the state-owned banks, institutional and regulatory framework, and the safety net mechanisms and deposit insurance governing the system. It is suggested the reform of the pension system is crucial at this juncture, given that the current pay-as-you-go social security public pension system, is not fiscally sustainable from an actuarial, and benefits payment perspective, and, because the current system, even at its best, delivers very low returns on pension investment funds. Most importantly, for both the public, and private systems, the investment regime should permit heavy weighting in foreign hard currency securities.